Unveiling the mechanisms of neuropathic pain suppression: perineural resiniferatoxin targets Trpv1 and beyond - Safa Shehab; Hayate Javed; Aishwarya Mary Johnson; Saeed Tariq; Challagandla Anil Kumar; Bright Starling Emerald (Frontiers Media S.A., 2023)
Neuropathic pain arises from damage or disorders affecting the somatosensory system. In rats, L5 nerve injury induces thermal and mechanical hypersensitivity/hyperalgesia. Recently, we demonstrated that applying resiniferatoxin (RTX) directly on uninjured L3 and L4 nerves alleviated thermal and mechanical hypersensitivity resulting from L5 nerve injury. Herein, using immunohistochemistry, Western blot, and qRT-PCR techniques, we reveal that perineural application of RTX (0.002%) on the L4 nerve substantially downregulated the expression of its receptor (Trpv1) and three different voltage-gated ion channels (Nav1.9, Kv4.3, and Cav2.2). These channels are found primarily in small-sized neurons and show significant colocalization with Trpv1 in the dorsal root ganglion (DRG). However, RTX treatment did not affect the expression of Kv1.1, Piezo2 (found in large-sized neurons without colocalization with Trpv1), and Kir4.1 (localized in satellite cells) in the ipsilateral DRGs. Furthermore, RTX application on L3 and L4 nerves reduced the activation of c-fos in the spinal neurons induced by heat stimulation. Subsequently, we investigated whether applying RTX to the L3 and L4 nerves 3 weeks before the L5 nerve injury could prevent the onset of neuropathic pain. Both 0.002 and 0.004% concentrations of RTX produced significant analgesic effects, while complete prevention of thermal and mechanical hypersensitivity required a concentration of 0.008%. Importantly, this preventive effect on neuropathic manifestations was not associated with nerve degeneration, as microscopic examination revealed no morphological changes. Overall, this study underscores the mechanisms and the significance of perineural RTX treatment applied to adjacent uninjured nerves in entirely preventing nerve injury-induced neuropathic pain in humans and animals.